A novel S-box-based postprocessing method for true random number generation - Avaroglu, Erdinc; Tuncer, Taner (Tubitak Scientific & Technological Research Council Turkey, 2020)
The quality of randomness in numbers generated by true random number generators (TRNGs) depends on the source of entropy. However, in TRNGs, sources of entropy are affected by environmental changes and this creates a correlation between the generated bit sequences. Postprocessing is required to remove the problem created by this correlation in TRNGs. In this study, an S-box-based postprocessing structure is proposed as an alternative to the postprocessing structures seen in the published literature. A ring oscillator (RO)-based TRNG is used to demonstrate the use of an S-box for postprocessing and the removal of correlations between number sequences. The statistical properties of the numbers generated through postprocessing are obtained according to the entropy, autocorrelation, statistical complexity measure, and the NIST 800.22 test suite. According to the results, the postprocessing successfully removed the correlation. Moreover, the data rate of the bit sequence generated by the proposed postprocessing is reduced to 2/3 of its original value at the output.
Keywords: Ring oscillator; random number; postprocessing; S-box; statistical test